Sustainable Construction: Water Use in Residential Buildings in Portugal - Amado, Miguel Pires; Barroso, Luis Marques (International Journal of Sustainable Construction Engineering and Technology, 2013)
Water is the most important resource to all life on our planet. The impact that buildings have on the consumption of this resource throughout their life cycle (planning, construction, operation and deconstruction) but mainly during the operation phase, has resulted in very high and unsustainable consumption patterns. Sustainable development, while a long-term goal, requires that the preservation of natural resources becomes a central point of any project strategy. Water is of vital importance to human life, it should be preserved to ensure its availability for a long period of time. However, little concern has been given to the importance of introducing a selection of more efficient solutions to save water in buildings and consequently increase sustainability in the construction sector. In this context it is on the design phase that the main resource saving water measures should be considered. Research on saving water involves an analysis of quantitative and qualitative measures and their adaptation to different contexts. Nowadays there are systems of voluntary certification of sustainable construction, which can help the design phase to achieve sustainability. This paper discusses a set of measures to reduce water consumption and enable a more efficient use of this resource in residential buildings. The measures presented are focused on user awareness campaigns, systems of rainwater and grey water recycling, the use of more efficient devices and reduction of leaks. The measures are analyzed and compared taking into account the consumption patterns for each device both inside and outside a domestic building and its effective reduction in water consumption